Improving Immersive Experiences in Telecommunication with Motion Parallax - Zhang, Cha; Florencio, Dinei; Zhang, Zhengyou (IEEE Signal Processing Magazine, 2011)
Human sensorial perception of the surrounding environment is very intricate and only partially understood. Visual depth perception, for example, is often attributed to stereo vision. However, if we close one eye, it becomes immediately obvious how much depth information we acquire from other mechanisms. One of these mechanisms is motion parallax, i.e., the fact that the relative apparent positions of objects change when we move our viewpoint. Traditional three-dimensional television (3DTV) systems provide carefully edited stereo video but often lack the capability of rendering any motion parallax. Similar to the visual experience, our audio experience is also affected by our body motion. Indeed, in addition to information about the environment captured by two ears with a fixed head position, we also capture (often, unconsciously) a richness of information about the environment by moving our heads to sample the sound field around us.